Ecology, policy, and politics : human well-being and the natural world - O'Neill, John, 1956- (Routledge, 1993)
Revealing flaws in both 'green' and market-based approaches to environmental policy, O'Neill develops an Aristotolian account of well-being. He examines the implications for wider issues involving markets, civil society and politics.